Liturgie als performative Trinitätstheologie - Kopp, Stefan (Münchener theologische Zeitschrift, 2025)
The address of the Father by the Son in the Holy Spirit (ad Patrem - per Filium - in Spiritu) can be identified as the grammar of Christian prayer language. This is particularly evident in presidential prayers and has been firmly established in both Eastern and Western liturgical traditions since early Christianity. However, Trinitarian prayer should not be understood as the application of dogmatic clarifications but rather as a source of inspiration for them, unfolding a performative-relational dynamic within the liturgy.